From the theory to practice: Five years of urban regeneration workshops - Raimundo Bambó-Naya; Pablo de la Cal-Nicolás; Carmen Díez-Medina; Sergio García-Pérez; Javier Monclús-Fraga (OmniaScience, 2018)
The aim of this communication is to present the experience of four academic courses in the subject of Integrated Urban and Landscape Design, taught in the framework of the Master in Architecture of the School of Engineering and Architecture of the University of Zaragoza. It addresses urban regeneration interventions in vulnerable areas of the consolidated city with approaches to teaching innovation in the academic field and in the topic of user participation. The workshop methodology is explained in detail, paying more attention to the process followed than to the specific results of the workshop. The different stages of the process are presented: previous phase and selection of the study area, phase of analysis and diagnosis, phase of proposals, where a joint work is carried out with vision of action in the whole of the neighbourhood, and phase of presentation of the results to the Neighbours. Finally, some future challenges of this workshop are outlined.